Kajian Residu dan Deteksi Residu Antibiotik Norfloksasin dan Tilosin pada Ayam Broiler: Kajian Artikel: Kajian Residu dan Deteksi Residu Antibiotik Norfloksasin dan Tilosin pada Ayam Broiler - Wibisono, Cahyo - (VITEK : Bidang Kedokteran Hewan, 2024)
Antibiotics are drugs that are often used in the chicken farming industry, especially broiler chickens, to treat bacterial infections and secondary infections caused by bacteria. Bacteria are one of the microorganisms that cause digestive and respiratory tract diseases in broiler chickens. The use of antibiotics is increasing every year in relation to treating bacterial infections. The combination antibiotic norfloxacin and tylosin which has a synergistic effect in the antibacterial spectrum and is complementary in the mechanism of action of the drug is often used to treat broiler chickens infected by Gram-positive and Gram-negative bacteria. Norfloxacin is a florquinolone antibiotic which has a broad spectrum, while tylosin is a macrolide antibiotic which also has a broad spectrum. combination of norfloxacin and tylosin in commercial poultry farming in Indonesia. This research aims to find out how many cases of residue and detection of norfloxacin and tylosin residues as well as knowing the levels of norfloxacin and tylosin residues in broiler chickens that exceed the Maximum Residue Limit (BMR) referring to SNI 2000. and also aims to increase awareness of broiler chicken breeders and consumers about effects of norfloxacin and tylosin residues on broiler chicken products. Norfloxacin and tylosin residues in broiler chickens were found in several literatures, both in cases of residues and residue detection. From 2010 to 2023, several studies even found no cases of residues of the antibiotics norfloxacin and tylosin in broiler chickens.